How children learn language - O'Grady, William (Cambridge : New York : Cambridge University Press, 2005)
"In this engaging and accessible book, William O'Grady provides a highly readable overview not only of the language acquisition process itself, but also of the ingenious experiments and techniques that researchers use to investigate this mysterious phenomenon. It will be ideal for anyone - parent or student - who is curious about how language works and how it is learned."
Includes bibliographical references (p. 218-237) and index.
Keywords: Language acquisition; Langage -- Acquisition; Spracherwerb